2022
DOI: 10.3389/fpubh.2022.935040
|View full text |Cite
|
Sign up to set email alerts
|

Regional disparity in epidemiological characteristics of adolescent scoliosis in China: Data from a screening program

Abstract: ObjectiveWe investigated regional disparities in rates of scoliosis among adolescents in western and eastern China and the dominant factors underlying these disparities.MethodsThis cross-sectional study used data from a school scoliosis screening program conducted in two typical areas: Yangpu District of Shanghai (eastern China) and Tianzhu Tibetan Autonomous County of Gansu Province (western China), during October 2020 to February 2021. Participants included adolescents aged 12–16 years (4,240 in Shanghai and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(41 reference statements)
2
1
0
Order By: Relevance
“…Furthermore, our study found the highest prevalence of IS in Northwest China, which aligns with the findings of an epidemiological study published in 2022 in China [42], which revealed a higher prevalence of adolescent scoliosis in the western region (Gansu province) than in the eastern region (Shanghai province) [42]. This regional difference may be attributed to variations in socioeconomic development levels.…”
Section: Estimated Prevalence and Cases Of Is Among Chinese Children ...supporting
confidence: 90%
“…Furthermore, our study found the highest prevalence of IS in Northwest China, which aligns with the findings of an epidemiological study published in 2022 in China [42], which revealed a higher prevalence of adolescent scoliosis in the western region (Gansu province) than in the eastern region (Shanghai province) [42]. This regional difference may be attributed to variations in socioeconomic development levels.…”
Section: Estimated Prevalence and Cases Of Is Among Chinese Children ...supporting
confidence: 90%
“…This survey conducted through the SSS found that the overall prevalence of IS among 7- to 19-year-olds in Yunnan Province is 1.10%, which is slightly higher than the national prevalence rate (1.02%). However, it falls within the range of prevalence rates observed in different provinces in China (ranging from 0.11% to 2.64%) ( 9 , 10 , 34 , 35 ). Research indicates that the prevalence of AIS is associated with various factors, such as ethnicity, altitude of residence, and socioeconomic status ( 6 , 35 ).…”
Section: Discussionsupporting
confidence: 56%
“…The prevalence is higher in females than in males, with female-to-male ratios ranging from 1.5 to 11 ( 7 , 8 ). In China, the prevalence of AIS is reported to be between 0.11% and 2.6%, with most data originating from economically developed eastern and southern regions, while there is limited reporting of AIS prevalence in western China ( 9 , 10 ). Yunnan, located on the southwestern border of China and situated on the Yunnan-Guizhou Plateau, is home to 26 different ethnic groups, making it the province with the most diverse national minority in China.…”
Section: Introductionmentioning
confidence: 99%
“…The onset age of adolescent idiopathic scoliosis is 9–10 years for girls and 11–12 years for boys. Adolescent idiopathic scoliosis (AIS) is the most common form of scoliosis, with a global prevalence ranging from 2 to 3% to 5.2% [ 1 , 2 , 3 , 4 , 5 ]. AIS is classified according to the Cobb angle value and the location and orientation of the pathological curve [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%